Efforts to Improve Students' Creativity and Learning Outcomes through the Demonstration Method in Creative Dance Using Property at Grade IX G SMP Negeri 2 Pulau Punjung - Darvita, Eni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
This research is attracted by the essence of learning Cultural Arts, namely to provide knowledge to students how they interact with their environment. These interactions creativity arises as a form of personality formation, skills, and intellectual development of students. Learning Arts and Culture also plays an important role in the education of insight, skills, and attitudes from an early age for students. However, in the process of teaching and learning Arts and Culture, what is expected is not in accordance with reality. The author uses the classroom action research conducted by the teacher in their own class by designing, implementing, and reflecting on actions in a participatory manner with the aim of improving the learning process in the classroom so that student activities and learning outcomes can increase. The research was conducted in class IX G of SMP Negeri 2 Pulau Punjung on the subject of Cultural Arts with the material